Frequency‐Selective Manipulations of Spins allow Effective and Robust Transfer of Spin Order from Parahydrogen to Heteronuclei in Weakly‐Coupled Spin Systems. Issue 3 (28th December 2021) - Pravdivtsev, Andrey N.; Hövener, Jan‐Bernd; Schmidt, Andreas B.
Abstract: We present a selectively pulsed (SP) generation of sequences to transfer the spin order of parahydrogen (pH2 ) to heteronuclei in weakly coupled spin systems. We analyze and discuss the mechanism and efficiency of SP spin order transfer (SOT) and derive sequence parameters. These new sequences are most promising for the hyperpolarization of molecules at high magnetic fields. SP‐SOT is effective and robust despite the symmetry of the 1 H‐ 13 C J‐couplings even when precursor molecules are not completely labeled with deuterium. As only one broadband 1 H pulse is needed per sequence, which can be replaced for instance by a frequency‐modulated pulse, lower radiofrequency (RF) power is required. This development will be useful to hyperpolarize (new) agents and to perform the hyperpolarization within the bore of an MRI system, where the limited RF power has been a persistent problem. Abstract : More spin order : We propose a new generation of frequency‐selective methods for parahydrogen spin order transfer to heteronuclei magnetization. The novel sequences require less RF power and hence are well‐suited for implementations on MRI systems. Moreover, they are most effective and robust as undesired J‐couplings are suppressed during the polarization transfer and the symmetry of the 1 H‐ 13 C coupling pattern plays no role anymore.